2019
DOI: 10.1029/2019jd030329
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Surface and Stratospheric Impacts of Geoengineering With Different SO2 Injection Strategies

Abstract: Geoengineering with stratospheric sulfate aerosols can, to some extent, be designed to achieve different climate objectives. Here we use the state‐of‐the‐art Community Earth System Model, version 1, with the Whole Atmosphere Community Climate Model as its atmospheric component (CESM1(WACCM)), to compare surface climate and stratospheric effects of two geoengineering strategies. In one, SO2 is injected into the tropical lower stratosphere at the equator to keep global mean temperature nearly constant under an R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
137
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(154 citation statements)
references
References 61 publications
14
137
3
Order By: Relevance
“…Details of the regional hydroclimate response will also depend on the geoengineering strategy employed. For example, experiments with CESM1(WACCM) in which only equatorial injection was used and interhemispheric temperature gradients were not maintained, actually exhibit an increase in precipitation over India during JJA Kravitz et al ( their Fig. 9b).…”
Section: Resultsmentioning
confidence: 99%
“…Details of the regional hydroclimate response will also depend on the geoengineering strategy employed. For example, experiments with CESM1(WACCM) in which only equatorial injection was used and interhemispheric temperature gradients were not maintained, actually exhibit an increase in precipitation over India during JJA Kravitz et al ( their Fig. 9b).…”
Section: Resultsmentioning
confidence: 99%
“…Under RCP8.5, sea ice extents in high latitudes experience rapid decrease during this century, while GLENS largely maintains the high‐latitude sea ice in both hemispheres (Figure S4, also see Kravitz et al, ). However, the seasonal temperature shift at high latitudes under GLENS has a significant effect on the seasonal cycle of sea ice change.…”
Section: Shifts In the High‐latitude Climate Seasonal Cyclementioning
confidence: 92%
“…The stratospheric heating could have significant dynamic effects on many aspects of the climate system (Ferraro et al, ; Ferraro et al, ; Richter et al, ; Visioni et al, ), including Northern Hemisphere (NH) winter warming that has been observed after large volcanic eruptions (Driscoll et al, ; Robock & Mao, ; Shindell et al, ; Wunderlich & Mitchell, ). Although volcanic eruptions are an imperfect analog of SAG, SAG‐induced stratospheric dynamic change could also lead to the NH winter warming (Rasch et al, ; Kravitz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, for off-equatorial injection that still results in similar levels of global mean cooling, the phase and magnitude of the QBO remain relatively unchanged ( fig. 2), and some of the side effects experienced under equatorial injection do not materialize 58 .…”
Section: Uncertainty and The Basis For Confidence In Solar Geoengineementioning
confidence: 99%
“…By modifying several of these degrees of freedom -that is, factors related to the deployment strategy -it may be possible to design SAG to achieve climate outcomes beyond solely reducing global mean temperature 19,38,49,59 . For example, if SAG was to be deployed only in the equatorial regions, this would prevent the rise in global mean temperature 58 but have the side effect of residual polar warming 8 ( fig. 3).…”
Section: Uncertainty and The Basis For Confidence In Solar Geoengineementioning
confidence: 99%